Pengaruh Posisi, Jumlah Layer Dan Mutu Kayu Terhadap Balok Laminasi Kayu Mahang Dan Kayu Meranti - Indriyani Puluhulawa (Jurnal Teknik Sipil, 2018)
Reduced forest products cause also reduced of large-dimensional wood that has high quality. One alternative to solve the problem is by doing laminate engineering by combining different quality wooden layers into specific sized beams as desired. The type of wood and the position of layer give effect to the laminate beam capacity. The aim of this research was to find out the flexural capacity (MOR) of Mahang and Meranti wood laminated beams which layers were varied which then the result of the laminated beam was compared with the solid beams. There were 3 types of laminate specimens made with dimension 5x7x76 cm3 which consisted of 7 layers; BL K1 beam consisted of 2 layers of Meranti wood at the top and bottom of the beam and 5 layers of Mahang in the middle; BL K2 beam consisted of 4 layers of Meranti wood at the top and bottom of the beam, and 3 layers of Mahang in the middle; and BL K3 beam consisted of 6 layers of Meranti wood at the top and bottom of the beam and 1 layer of Mahang in the middle. The test results showed that the use of wood of higher specific gravity at the outermost layer has increased the flexural capacity (MOR) and modulus of elasticity (MOE), particularly in laminated beams (Meranti wood and Mahang wood) with the same numbers of layers. Moreover, in same number or greater layer proportion between Mahang and Meranti wood, the result showed the increased of MOR and MOE of laminated beams compared with solid beam that has low specific gravity (Mahang).